Antimicrobial Susceptibility of Borrelia burgdorferi Sensu Lato: An In vitro Study Approach - Klaus-Peter Hunfeld; Peter Kraiczy; Douglas E. Norris; Benedikt Lohr (Research Perspectives of Microbiology and Biotechnology Vol. 2, 2024)
This review summarizes about In vitro susceptibility testing methods and In vitro interactions of B. burgdorferi s.l. with antimicrobial agents and antibiotic medium preparations. The multisystem illness known as human Lyme borreliosis (LB) can advance in phases. Hard ticks of the Ixodes ricinus complex that have contracted the spirochete Borrelia burgdorferi sensu lato are the carriers of the causative agents. Today, LB is considered the most important human tick-borne illness in the Northern Hemisphere. The causative agent was identified and successfully isolated in 1982 and, shortly thereafter, antibiotic treatment was found to be safe and efficacious. Since then, various In vitro studies have been conducted in order to improve our knowledge of the activity of antimicrobial agents against B. burgdorferi s.l. The full spectrum of In vitro antibiotic susceptibility has still not been defined for some of the more recently developed compounds. Moreover, our current understanding of the In vitro interactions between B. burgdorferi s.l. and antimicrobial agents, and their possible mechanisms of resistance remains very limited and is largely based on In vitro susceptibility experiments on only a few isolates of Borrelia. The potential processes underlying the In vitro survival of spirochetes exposed to antimicrobial drugs in the presence of animal and human cell lines are much less understood. There have only been a modest number of cell culture experiments and laboratory research carried out. In addition to ongoing clinical trials on the optimum treatment regimen for LB, further basic research is urgently needed in order to better understand possible genetic or phenotypic mechanisms of persistence in Borrelia spp. This review summarizes what is and what is not known about the In vitro susceptibility of B. burgdorferi s.l. It aims to shed light on the known unknowns that continue to fuel current debates on possible treatment resistance and mechanisms of persistence of Lyme disease spirochetes in the presence of antimicrobial agents.